Social Work students’ attitudes towards gender equality in Namibia: Results from an exploratory study - Mathews, John; Muinjangue, Ester; Nashandi, Johanna; Rukambe, Zelda (Journal for Studies in Humanities and Social Sciences, 2014)
This manuscript explores the attitudes towards gender equality of students studying social work in Namibia. While previous published research has explored social work students’ attitudes toward sexism and gender equality, no published research presents the perspectives of students in a Southern African context. The Ambivalent Sexism Inventory (ASI) was used as the main data collection tool. This 22-item instrument measures levels of benevolent and hostile sexism and is supported with firm psychometric evidence, including established validity in international settings and in multiple languages. Results presented are based on a sample of 154 undergraduate social work students in an accredited social work degree programme at a Namibian public university. Overall, the results indicate above average levels of sexism, with higher scores for benevolent sexism than hostile sexism. Using bivariate analyses, the findings indicate that older students, married students, and those in the advanced stages of the degree programme (years 3-4) hold more positive attitudes related to gender equality, and thus hold less sexist views. Suggestions for addressing negative beliefs about gender equality in terms of curricular integration and increasing opportunities for student exposure to positive imagery are discussed.